A Critical Analysis Of Customs-Business Partnership Compliance The Import And Export Enterprises With Customs Law And Regulation - NGUYEN, V. D; AQUINO, P. G; HONG LE, D. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This research systematically presents the multifarious information and data from secondary and primary sources to provide the results of articles and papers relative to Customs-Business Partnership that affect the compliance of import and export enterprises based on customs law and regulation. The authors have established the theoretical model to analyze the Customs-Business Partnership in Vietnam. The authors conducted a survey involving 202 enterprises from the cities of Hanoi, Hai Phong, Dong Nai, Ho Chi Minh, Binh Duong, and Vung Tau, respectively, on August 2018. By using and performing a multivariate regression method and analysis, the paper gives predictions following the Binary logistic regression. RESUMEN Esta investigación presenta sistemáticamente la información y datos múltiples de fuentes secundarias y primarias para proporcionar los resultados de artículos y documentos relacionados con la Asociación de Aduanas y Negocios que afectan el cumplimiento de las empresas de importación y exportación de acuerdo con las leyes y regulaciones aduaneras. Los autores han establecido el modelo teórico para analizar la Asociación de Aduanas y Negocios en Vietnam. Los autores realizaron una encuesta con 202 empresas de las ciudades de Hanoi, Hai Phong, Dong Nai, Ho Chi Minh, Binh Duong y Vung Tau, respectivamente, en agosto de 2018. Mediante el uso y la realización de un método y análisis de regresión multivariante, el documento da predicciones siguiendo la regresión logística binaria